1995
DOI: 10.1111/j.1939-1676.1995.tb01092.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Renin‐Angiotensin System in Dogs With Asymptomatic and Mildly Symptomatic Mitral Valvular Insufficiency

Abstract: The renin-angiotensin system has important pathophysiologic implications in the development of congestive heart failure. The activity of the renin-angiotensin system early in the course of heart disease and heart failure in dogs was evaluated by measuring the plasma renin activity (PRA) and plasma aldosterone concentration (PAC) in 1 8 Cavalier King Charles Spaniels with asymptomatic or mildly symptomatic mitral valvular insufficiency, and in 1 8 healthy Cavalier King Charles Spaniels. All dogs were unmedicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
0
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 12 publications
6
46
0
3
Order By: Relevance
“…Intracardiac angiotensin converting enzymes and angiotensin II production are stimulated by diastolic wall stress induced by the low pressure volume overload of mitral regurgitation (Dell'Italia et al, 1995). Also, early activation of the renin-angiotensin system has been demonstrated in dogs with asymptomatic or mildly symptomatic mitral valve insufficiency (Pedersen et al, 1995). Hence, it is possible that the pathological changes of left AV valves in broiler chickens may initiate a sequence of profound hormonal and haemodynamic changes leading to heart failure.…”
Section: Discussionmentioning
confidence: 98%
“…Intracardiac angiotensin converting enzymes and angiotensin II production are stimulated by diastolic wall stress induced by the low pressure volume overload of mitral regurgitation (Dell'Italia et al, 1995). Also, early activation of the renin-angiotensin system has been demonstrated in dogs with asymptomatic or mildly symptomatic mitral valve insufficiency (Pedersen et al, 1995). Hence, it is possible that the pathological changes of left AV valves in broiler chickens may initiate a sequence of profound hormonal and haemodynamic changes leading to heart failure.…”
Section: Discussionmentioning
confidence: 98%
“…It is well accepted that plasma renin and/or Ang II level is elevated in CHF due to rapid pacing [27], cardiac infarction [28,29], mitral valvular diseases [30], or human congestive heart failure [31]. On the other hand, Iwanaga et al [32] reported that the plasma Ang II level was within a normal range in salt-sensitive hypertension-induced heart failure, which indicates that salt-induced heart failure may not have high RAS activity.…”
Section: Discussionmentioning
confidence: 95%
“…Its contribution to the development of hypertension (HT) and congestive heart failure (CHF) has long been recognized (Kunita et al, 1976;Nicholls et al, 1993;Pedersen et al, 1995;Roche et al, 2002). Results from our previous research (Mochel et al, 2013) have shown that variables of the renin cascade and BP oscillate with a 24-h periodicity in dogs fed a regular diet at 07:00 h. In this earlier study, dietary sodium was found to have an influence on the chronobiology of RA and urinary aldosterone, indicating that varying feeding schedules could also impact the chronobiology of the renin cascade.…”
Section: Discussionmentioning
confidence: 99%